Otoplasty and Auricular Reconstruction - Siegert, Ralf; Magritz, Ralph (Facial Plastic Surgery, 2019)
Due to the variety of abnormalities, surgery of the auricle is one of the most complex challenges in facial plastic surgery. They reach from mild protruding ears or isolated abnormalities of the supporting structures, mainly the helical rim and antihelix, over cup ear deformities and miniears all the way to severe microtia and anotia. In this article, the authors present a short overview of auricular abnormalities and malformations and their treatment options based on their experiences gained over three decades of special service for patients with auricular malformations.
Keywords: auricle; malformation; rib cartilage; auricular reconstruction